2013
DOI: 10.1021/jp312272p
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Quenching Mechanism of a Terthiophene Acid Dye Bound to Monodisperse CdS Nanocrystals: Electron Transfer versus Concentration Quenching

Abstract: Oleate-capped CdS nanocrystals (NCs) dispersed in dichloromethane were found to quench the excited-state fluorescence of the terthiophene derivative 3′,4′-dibutyl-5″-phenyl-[2,2′:5′,2″-terthiophene]-5-carboxylic acid (1-CO 2 H). Infrared and 1H NMR spectroscopies provided evidence that 1-CO 2 H substitutes for oleate on the surface of the CdS NCs. Upon binding, the fluorescence of 1-CO 2 H is quenched, and the 1H NMR lines from 1-CO 2 H are broadened. The importance of the carboxylate group in binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Further quencher addition caused a decrease in emission until a plateau was reached at a dye:ZnO NC of approximately two. The general shape of the Stern Volmer graphs observed for these dyes paralleled those reported in earlier studies, where the suggested causes were concentration quenching 21 or competition between dye binding sites that were or were not quenched. 3,4 The current work focused on the ultrafast quenching kinetics at a dye to ZnO NC of 2:1 in order to minimize any complications attributed to dye-dye interactions.…”
Section: Resultssupporting
confidence: 83%
“…Further quencher addition caused a decrease in emission until a plateau was reached at a dye:ZnO NC of approximately two. The general shape of the Stern Volmer graphs observed for these dyes paralleled those reported in earlier studies, where the suggested causes were concentration quenching 21 or competition between dye binding sites that were or were not quenched. 3,4 The current work focused on the ultrafast quenching kinetics at a dye to ZnO NC of 2:1 in order to minimize any complications attributed to dye-dye interactions.…”
Section: Resultssupporting
confidence: 83%
“…Using eq , with k q = 1.5 × 10 7 s –1 , we calculate that m max = 16 could achieve P NC→9‑ACA = 0.95 if the fast 134 ps decay component is neglected. Possible experimental approaches to increase m max include changing the NC preparation conditions so the 9-ACA displaces a carboxylic acid ligand rather than a phosphonic acid ,, or changing the ligand exchange conditions to boost [9-ACA] LEX and/or make displacement of the ODPA more favorable. We anticipate that optimization of the ligand exchange conditions will increase m max and the UC yield as well.…”
Section: Discussionmentioning
confidence: 99%
“…35 This is well below the anodic peak potential determined for T3 absorbed on planar indium-tin oxide (ITO) in the same media, E p = 1.03 V vs SCE (Figure S8), and the resulting couple formed upon continued anodic scanning, E 1/2 = 0.91 V vs SCE (Figure S9). 36,37 At the TiO 2 -T3 photoanode, photocurrent arises from the thermodynamically favorable oxidation of H 2 Q to semiquinone, HQ •+ , then to quinone, Q, by two sequential T3 •+ radical cation reductions. T3 •+ is formed after electron injection by the chromophore's excited state, T3*, into the conduction band of TiO 2 .…”
Section: ■ Xps and Ph Titration Of T3-ru-otfmentioning
confidence: 99%
“…This is well below the anodic peak potential determined for T3 absorbed on planar indium-tin oxide (ITO) in the same media, E p = 1.03 V vs SCE (Figure S8), and the resulting couple formed upon continued anodic scanning, E 1/2 = 0.91 V vs SCE (Figure S9). , …”
Section: Xps and Ph Titration Of T3-ru-otfmentioning
confidence: 99%